Choke point [large type] - Pearson, Ridley (A Risk Agent Novel Series, 2013)
Hired to investigate allegations of a sweat-shop operation in Amsterdam that is enslaving young girls, Knox and tech information expert Grace Chu embark on a rescue mission that is challenged by a crime organization that has seduced local neighborhoods with showy goodwill practices.